A Study of Selected Pre-Colonial Political Entities in the Niger- Benue Confluence Region of Nigeria - Hadizat Audu Salihu (International Studies Journal)
The Niger-Benue confluence region is multi-lingual with diverse ethnic groups and political entities. The region is well known for its abundant natural resources such as navigable inland waterways, mountains and fertile soil. During the pre-colonial period, the area witnessed migrations of different groups of people with varying socio-economic and political system into the area which increased the political diversity and activities in the confluence region. The study is aimed at examining some selected political entities in the Niger-Benue confluence area in other to assess their political structures and their impact on the region. The methodology employed in this study is the historical method of analysis which involved the use of both primary and secondary sources of information. The study revealed that there were dynamics in the political system operated in the Niger-Benue confluence region in the pre-colonial era which impacted other ethnic group’s political structures and contributed to the development of the region before British colonial rule. The study concludes that the Niger-Benue confluence area like many regions in Nigeria had diverse political entities that have contributed to its development before, during and after colonial rule. It, however, recommends that political institution in the Niger-Benue confluence area is an integral part of its history which has to be studied in other to understand its metamorphosis, change and growth over time.